A Preliminary Survey of the Eastern Harbor, Alexandria, Egypt, Including a Comparison of Side Scan Sonar and Remote Viewing - Schwartz, Stephan Andrew (Journal of Scientific Exploration, 2021)
This paper reports a preliminary survey of one of humanity's most historic harbors–Alexandria, Egypt. It constitutes one phase of a broader joint land/sea examination of the largest and most famous city to bear Alexander the Great's name. The research overall had two goals: 1) to resolve locational uncertainties concerning the city's past configuration, particularly its Ptolemaic antecedents; and 2) to compare electronic remote sensing survey technologies with Remote Viewing generally, and the applications methodology developed by the Mobius Groups specifically. In the area of the Eastern Harbor, the aim of the research was: 1) the location of the ancient shore line; the locaton of and predictive description of several sites including the island of Antirrhodus and the Emporium/Poseidium/Timonium complex; a palace complex associated with Cleopatra; and a further elaboration, both in terms of location and predictive description, of the Pharos lighthouse area; 2) a comparison of Remote Viewing and side scan sonar data after each approach had surveyed the same area. This paper describes the probable location of the Emporium, the Poseidium, and the Timonium, the palace complex of Cleopatra, the island of Antirrhodus, a site at the tip of Fort Sisila (known prevously as Point Lochias), new discoveries pertaining to the lighthouse, andd an associated temple. The most important discovery though is the identification and location of the ancient seawall which extends some 65 meters farther out into the harbor than was previously suspected, and whoe location resolves a key piece in the puzzle of the ancient city's layout. The discoveries reported here were principally the result of Remote Viewing. Except for one clear "hit," side scan sonar proved unproductive because of the large amount of particulate in the water.